Transformation of Microfinance Institutions into Rural Banks - Vastigia Zahratul Fuadah (Proceedings Series on Social Sciences & Humanities, 2023)
As time progresses there is more and more growth in various kinds of economic activities in indonesia. one of them is in the banking sector. more and more microfinance institutions continue to grow in indonesia. microfinance institutions are the most crucial and important financial institutions for the people in indonesia. Microfinance institutions also have opportunity to transform into people's credit banks. microfinance institutions can be divided into 2 parts, namely conventional microfinance institutions and sharia microfinance institutions. likewise, people's credit banks are divided into 2, namely sharia people's credit banks and conventional people's credit banks. then regarding factors needed from the process of changing the transformation of Microfinance Institutions into People's Credit Banks, to the legal certainty of changing the transformation of Microfinance Institutions into People's Credit Banks. In accordance with the title and problems to be discussed in this study, in order to provide useful results, type of research used by the author is Empirical Juridical research. Juridical-empirical research is legal research on the enactment or implementation of normative legal provisions directly on each specific legal event that occurs in society. The Legal Basis of Microfinance Institutions in Indonesia is that the business activities and operations are regulated in official regulations contained in the Microfinance Institutions Law and Government Regulations. Furthermore, MFIs also receive supervision from the Financial Services Authority (OJK). It is expected to know and criticize what factors are needed in the process of changing the transformation of Microfinance Institutions into Rural Banks, as well as the legal certainty of these issues.